PENGEMBANGAN MODEL IDENTICAL DERLIVERY QUANTITY (IDQ) DALAM MANAJEMEN INVENTORI DENGAN PEMBAYARAN TERTUNDA BERBASIS SUKU BUNGA BANK - Muhammad Faishal; Chaerul Saleh (Fakultas teknik Universitas Muhammadiyah Jakarta, 2017)
Nowadays, manufacturing companies must have good product quality to compete in international market with minimum cost. To achieve this result, one of the supporting factors is product development with a good and efficient inventory system between company and its distributor. In developing the product and calculating some costs, the company usually use credit facility of conventional bank. The purpose of Identical Delivery Quantity (IDQ) model is to minimize total inventory cost for both company and its distributor that are mutually coordinated and cooperative. Then, this model is expanded with some models of interest rates. There are annuity, flat rate, and sliding rate. This propose solution has objective to minimize total inventory cost for both company and its distributor that considering the credit facilities. A numerical example from real case company was applied to this developed model. The result showed that the model of sliding rate is the lowest than others.